Blue toe syndrome as a first sign of systemic sclerosis. (5th January 2018) - Neuman, Rugina; Wabbijn, Marike; Guillen, Samara; Dees, Adriaan
Abstract : We describe an unusual case of blue toe syndrome as the primary and solitary manifestation of systemic sclerosis. The possible cause was long-term occupational exposure in construction work. Blue toe syndrome is a small vessel disease, characterised by the sudden development of painful, blue discolouration in one or more toes. The most common aetiology is atheroembolic disease; however, it can also appear in several conditions ranging from hypercoagulability disorders to underlying systemic diseases such as vasculitis or autoimmune diseases. Here, we describe the case of a 57-year-old man who presented with blue toe syndrome without underlying atheroembolic disease. He was found to have positive anticentromere antibodies, which indicated that systemic sclerosis was the likely primary underlying cause. An extensive systemic evaluation and a thorough physical examination revealed no other symptoms associated with systemic sclerosis. He was prescribed nifedipin and rosuvastatin, and showed complete resolution of symptoms after 3 months.